Al-Shāfi’ī’s position on analogical reasoning in Islamic criminal law: Jurists debates and human rights implications - Zakariyah, Luqman (Springer Netherlands, 2016)
Al-Sha¯fi’ı¯ (d. 204/820) has been unreservedly credited as one of the designers, if not the “master architect,” of uṣūl al-fiqh (Principles of Islamic jurisprudence). His most important scholarly work, Al-Risa¯lah (The Epistle), clearly demonstrates his cognitive creativity in this field. One of the methodologies for the decision of cases under Islamic law that Al-Sha¯fi’ı¯ championed is qiyās (analogical reasoning), which he equated with ijtihād (legal reasoning). His balanced approach invites further enquiry into the extensive use of qiyās in general and in criminal law in particular. The extent to which qiyās can be applied to Islamic criminal law depends upon the degree or typology of qiyās being used, taking into account the Islamic theory of criminology. This article will analyse the position of al-Sha¯fi’ı¯ in this regard. It will critically examine al-Sha¯fi’ı¯’s complex views on the use of qiyās as a method for establishing culpability under Islamic criminal law. It will then explore how his position corresponds to the human rights paradigm in the contemporary age. This article concludes that, while the use of qiyās in criminal law, especially in law of retaliation (qiṣāṣ) and predetermined punishments (ḥudūd) in accordance with al-Sha¯fi’ı¯’s approach is tantamount to incriminating a person based on less than certainty (yaqīn), it also represents the most promising way of protecting the right of victim.